2021
DOI: 10.1159/000514420
|View full text |Cite
|
Sign up to set email alerts
|

Avelumab in Combination with Axitinib as First-Line Treatment in Patients with Advanced Hepatocellular Carcinoma: Results from the Phase 1b VEGF Liver 100 Trial

Abstract: <b><i>Introduction:</i></b> Combining an immune checkpoint inhibitor with a targeted antiangiogenic agent may leverage complementary mechanisms of action for the treatment of advanced/metastatic hepatocellular carcinoma (aHCC). Avelumab is a human anti-PD-L1 IgG1 antibody with clinical activity in various tumor types; axitinib is a selective tyrosine kinase inhibitor of vascular endothelial growth factor receptors 1, 2, and 3. We report the final analysis from VEGF Liver 100 (NCT0328953… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 31 publications
2
30
0
Order By: Relevance
“…4 Several immune checkpoint inhibitor combi nation strategies have been studied for their potential to augment an antitumour immune response. [5][6][7][8][9][10] Hepatocellular carcinoma is associated with immune tolerance, which is potentially related to overexpression of cytokine pathways in the tumour microenvironment, resulting in the recruitment of immunosuppressive cells and the inhibition of cells associated with immune response. VEGF overexpression can inhibit T-cell function, increase myeloid-derived suppressor cells and…”
Section: Introductionmentioning
confidence: 99%
“…4 Several immune checkpoint inhibitor combi nation strategies have been studied for their potential to augment an antitumour immune response. [5][6][7][8][9][10] Hepatocellular carcinoma is associated with immune tolerance, which is potentially related to overexpression of cytokine pathways in the tumour microenvironment, resulting in the recruitment of immunosuppressive cells and the inhibition of cells associated with immune response. VEGF overexpression can inhibit T-cell function, increase myeloid-derived suppressor cells and…”
Section: Introductionmentioning
confidence: 99%
“…This result may be attributed to the difference in regimen, in which only one initial priming with anti-CTLA-4 was performed in the HIMALAYA Study. In addition, the hypertension, proteinuria, hand-foot skin reaction, and bleeding events, which are frequently observed in patients treated with anti-PD-1/PD-L1 antibody + anti-VEGF/TKI combination immunotherapy ( 4 - 6 ), were rarely observed.…”
Section: Results Of Phase 3 Himalaya Trialmentioning
confidence: 99%
“…The meta-analysis showed that the combined ORR ( 22 , 25 27 ) and DOR ( 25 , 27 ) of PD-1 combined with antiangiogenic inhibitors in hepatocellular carcinoma was HR=19.11, 95% CI=15.99, 22.22, I 2 = 92.7%, p=0.000 and HR=12.26, 95% CI=10.32, 14.21, I 2 = 95.7%, p=0.000. Clinical trials of F. Hoffmann-La Roche Ltd ( 22 ) showed that the ORR of PD-1 combined with antiangiogenic drugs and without PD-1 were HR=27.30, 95% CI=22.54, 32.48 and HR=11.90, 95% CI=7.35, 18.03.…”
Section: Resultsmentioning
confidence: 99%